2014
DOI: 10.1080/13811118.2013.833150
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation among Italian and Spanish Young Adults: The Role of Sexual Orientation

Abstract: The purpose of the current study was to identify demographic, social, and psychological variables associated with suicidal ideation in an Italian sample and a Spanish sample, taking into account the relevance of sexual orientation as a risk factor for suicide. Three hundred twenty gay and bisexual men, 396 heterosexual men, 281 lesbians and bisexual women, and 835 heterosexual women were recruited. In chi-square and multivariable logistic regression analyses we identified several consistent cross-national risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 40 publications
6
53
0
10
Order By: Relevance
“…Consistent with prior studies [18,23,24], we confirmed the hypothesis of finding a higher level of internalized homophobia in gay participants compared to lesbian ones. In the Portuguese context, sexism plays a dominant role in the social pressure to conform to heteronormative gender roles.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with prior studies [18,23,24], we confirmed the hypothesis of finding a higher level of internalized homophobia in gay participants compared to lesbian ones. In the Portuguese context, sexism plays a dominant role in the social pressure to conform to heteronormative gender roles.…”
Section: Discussionsupporting
confidence: 81%
“…Lower self-esteem has also been associated to suicidal ideation [16], and suicidal attempt [17]. Finally, recent studies show that past victimization experiences and IH have a significant direct effect on suicide ideation [18], indicating that when compared with non-LGB youth, LGB youth had increased odds of suicide ideation [19].…”
Section: Introductionmentioning
confidence: 99%
“…56 A study that compared heterosexual and lesbian/gay youths aged 16-25 found internalized negativity towards same-sex attraction to be related to higher levels of psychological distress (especially during the stage of coming out) but not directly to suicidal behaviour. 57 Internalized sexual stigma was found to have a significant effect on life repulsion as an aspect of suicide ideation in Spanish and Italian gay and lesbian individuals aged 18-35 years 58 , and to be positively associated with lifetime history of suicide attempts in transgender people (mean age 30 years) in Argentina. 59 To summarise, at the individual level, non-accepting attitudes of society and close network and related prejudices, stigma, victimization and discrimination may lead to internalized homo-/bi-/trans-phobia in sexual minority young persons; this, in turn, may exacerbate psychological distress and lead to self-hate feelings and suicidality.…”
Section: Close-network Level: Acceptance and Support From Family And mentioning
confidence: 96%
“…La ideación suicida y el intento de suicidio en adolescentes y jóvenes españoles y portugueses se han relacionado consistentemente con estas situaciones (Baiocco et al, 2014;Pereira y Rodrigues, 2015), así como la homofobia internalizada (Pereira y Rodrigues, 2015).…”
Section: Introductionunclassified